FACTORS AFFECTING PROGNOSIS OF TUBERCULOUS MENINGITIS IN SAIFUL ANWAR GENERAL HOSPITAL MALANG - Munir, Badrul; Prayudi, Firman; Setianto, Catur Ari; ., Siswanto (Malang Neurology Journal, 2020)
Background. The mortality rate of tuberculous meningitis (TBM) is approximately 20-41%. The prognosis is influenced by clinical and radiologic features, laboratory findings, and therapy. Objective. To report factors affecting the prognosis of TBM patients in Saiful Anwar Hospital.Methods. The study design was a retrospective cohort with consecutive sampling. Data were taken from medical records of 47 patients from 2016-2017. The prognostic value used modified rankin scale showing good (0-2) and poor prognosis (3-6). The impact of clinical, radiological, and laboratory factors were investigated by univariate analysis and multiple logistic regression. Results. In this study, good (n=21) and bad (n=26) prognosis were compared. Patients with good prognosis experienced more episodes of seizure than poor prognosis (17% vs 4%; p = 0.011). Focal neurologic deficits was more prevalent in poor prognosis (4% vs. 23%, p = 0.012). Meningeal enhancement was more common in poor prognosis (21% vs 42%; p= 0.038). From multivariate analysis, we found that seizure and focal neurological deficit are independent prognostic factors (p=0.023 dan p 0.033).Conclusion. Clinical factors influencing prognosis of TBM in Saiful Anwar Hospital are seizure and focal neurological deficit. Focal neurological deficit is a poor prognostic factor. However, seizure is a good prognostic factor. Keywords: prognostic factors, tuberculous meningitis